2017
DOI: 10.1016/j.ijdrr.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring disaster resilience within the hotel sector: A systematic review of literature

Abstract: A B S T R A C TWithin the tourism industry, the hotel sector's vulnerabilities are multi-faceted. This literature discussion scrutinizes how disaster and resilience is framed for the tourism sector, and, more specifically, how the concepts can be applied to the hotel sector. A synthesis of the literature points to the importance of prioritizing disaster resilience building for the hotel sector. The body of literature regarding disasters, tourism, and more specifically hotels, has increased over the last 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 69 publications
(147 reference statements)
1
143
1
7
Order By: Relevance
“…Natural hazards are common occurrences, and tourism is among those economic sectors that are most vulnerable to their impacts (Brown, Rovins, Feldmann‐Jensen, Orchiston, & Johnston, ). In this regard, vulnerability refers to “the extent to which a community, system or asset is susceptible to the damaging effects of a particular hazard” (Becken & Khazai, , p. 97).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural hazards are common occurrences, and tourism is among those economic sectors that are most vulnerable to their impacts (Brown, Rovins, Feldmann‐Jensen, Orchiston, & Johnston, ). In this regard, vulnerability refers to “the extent to which a community, system or asset is susceptible to the damaging effects of a particular hazard” (Becken & Khazai, , p. 97).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, preventing the disaster from onset is ideal but not always possible due to the number of vulnerabilities present at a destination and/or within its TBs. This pinpoints the importance of developing preparedness measures at the predisaster stage (Miller & Ritchie, ) and ensuring stakeholder collaboration aiming to manage the effects of disasters (Brown et al, ) including the negative impact on the consumer perception of a destination (Hystad & Keller, ). The postdisaster stages offer a learning opportunity for destinations and the tourism enterprises within (Wilkinson et al, ) and provide a medium to redefine the destination through (re‐) development (Seraphin, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The accommodation and F&B sector are able to service the needs of community needs after disasters (Hystad & Keller, 2006), such as using Airbnb accommodation to provide homes for tourists and aid workers (Hajibaba, Karlsson, & Dolnicar, 2017). Furthermore, informal (or small) tourism organizations (Biggs, 2011;Nieves et al, 2016;Orchiston, 2013;Prayag et al, 2018); and tourism resilience (Biggs, 2011;Orchiston, 2013;Orchiston et al, 2016) Hystad and Keller (2006), Cioccio and Michael (2007), Biggs (2011), Orchiston (2013), Ghaderi et al (2014), Prayag et al (2018), and Nieves et al (2016) (e.g., in family ownership) usually have lower capital investment than formal (or large) tourism organizations but have higher levels of social capital from the community (Biggs et al, 2012), which is found to be positively related with organizational resilience (Brown et al, 2017;Calgaro & Lloyd, 2008;Chowdhury et al, 2018).…”
Section: New Operational Routinesmentioning
confidence: 99%
“…The accommodation and F&B sector are able to service the needs of community needs after disasters (Hystad & Keller, ), such as using Airbnb accommodation to provide homes for tourists and aid workers (Hajibaba, Karlsson, & Dolnicar, ). Furthermore, informal (or small) tourism organizations (e.g., in family ownership) usually have lower capital investment than formal (or large) tourism organizations but have higher levels of social capital from the community (Biggs et al, ), which is found to be positively related with organizational resilience (Brown et al, ; Calgaro & Lloyd, ; Chowdhury et al, ).…”
Section: Dynamic Capabilities Approach To Achieve Resilience In Crisementioning
confidence: 99%
See 1 more Smart Citation